Risk Factors Associated With Medication Errors Among Patients Suffering From Chronic Disorders - Rasool, Muhammad Fawad; Rehman, Anees ur; Imran, Imran; Abbas, Sameen; Shah, Shahid; Abbas, Ghulam; Khan, Irfanullah; Shakeel, Sadia; Ahmad Hassali, Mohamed Azmi; Hayat, Khezar (Frontiers in Public Health, 2020)
Introduction: Medication errors are more common in patients suffering from chronic diseases. In under-developed countries like Pakistan overburden healthcare system, lack of disease-surveillance system, and shortage of healthcare staff are potential risk factors for medication errors. Objective: to assess the prevalence and risk factors associated with medication errors among patients suffering from chronic disorders in hospitals of south Punjab, Pakistan. Methodology: Multiple logistic regression analysis was used to assess the impact of different risk factors on prevalence of medication errors in patients suffering from chronic diseases. Results: A greater risk for occurrence of medication errors was associated with age ≥ 60 years (OR = 1.9; 95 % CI=1.3–3.1; p=0.001), Overburden (OR = 2.2; 95% CI=1.64-3.56; P<0.000), No. of prescribed drugs ≥ 5 (OR =1.74; 95% CI=1.02-2.64; p<0.000), comorbidities ≥ 3 (OR=2.6; 95% CI=1.72-3.6; p=0.003 ), CCI ≥ 1 (OR=1.31; 95% CI=0.49-1.84; p=0.004), and multiple prescribers to one patient (OR=1.12; 95% CI=0.64-1.76; p=0.001). Conclusion: Reduction of complexity in the act of prescribing by the introduction of automation, improved prescriber’s knowledge by education, use of on-line aid, and feedback control systems can help in the reduction of medication errors.